2019
DOI: 10.3390/ma12101590
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the In-Plane Mechanical Anisotropy of Magnesium Alloy AZ31B-O by VPSC–TDT Crystal Plasticity Model

Abstract: The in-plane mechanical anisotropy of magnesium alloy sheet, which significantly influences the design of the parts produced by Mg alloy sheets, is of great importance regarding its wide application. Though the stress–strain response and texture evolution have been intensively investigated, and the anisotropy of Mg alloy can be significantly substantiated by its R-value, which reveals the lateral response of a material other than the primary response. As a consequence, the conjunction of viscoplastic self-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The results demonstrated that the {10-12} extension twins are responsible for the main texture variations. Zhang [28] used VPSC to investigate the in-plane anisotropy of a Mg alloy AZ31B-O sheet. The hexagonal close-packed crystallographic structure, deformation twinning, and initial basal texture are responsible for the characteristic behavior of Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the {10-12} extension twins are responsible for the main texture variations. Zhang [28] used VPSC to investigate the in-plane anisotropy of a Mg alloy AZ31B-O sheet. The hexagonal close-packed crystallographic structure, deformation twinning, and initial basal texture are responsible for the characteristic behavior of Mg alloys.…”
Section: Introductionmentioning
confidence: 99%